Alienation, commitment and transcendence in three novels of Saul Bellow - Gargi, Arvind Kumar (My University, 1977)
The central point of this thesis is the theme of modern man's alienation from his surroundings as portrayed by Saul Bellow in three of his novels, Dangling Man, Henderson the Rain King and Humboldt's Gift. The individual is seen in Dangling Man as alienated from society, in Henderson the Rain King from nature, and in Humboldt's Gift from the spiritual reality. The relevance of Owen Barfield's thesis in his book Save the Appearances to Bellow's Henderson the Rain King is shown here to be important for our understanding of Bellow's concern with modern man's alienation. My thesis also shows Bellow's faith in man's capacity to solve his dilemma into which "civilization" with its emphasis on the scientific view of the phenomena has put him. Bellow's hero is determined to make a conscious commitment with society and nature that surround him. Only such commitment will give his life a meaning and purpose. But for Bellow this is not enough. My thesis shows how Bellow's hero in his latest novel, Humboldt's Gift,is in search of spiritual reality and how he decides to transcend his involvement with this world in order to relate with the world of soul. The anthroposophist Rudolph Steiner is seen as an influence upon Bellow in respect to his latest protagonist's search for the spiritual reality.
Keywords: Bellow, Saul.